Caring for the carer in the era of HIV diagnosis - Sempane, Lempye J. (HTS teologiese studies, 2013)
The care of terminally ill patients can be physically, emotionally as well as psychologically exhausting. In the era where everyone is busy with his or her hectic daily schedule, caring for someone diagnosed with HIV on her or his deathbed can be a daunting challenge. Caring for someone dying of AIDS does not only challenge the physical being but rather leaves the carer emotionally drained. What was of concern to the author was to see the struggle that the caregiver goes through whilst caring for the sufferer. More often than not, pastoral care and counselling concentrate mainly on the pain and the suffering of the sick person. In the process, pastoral care loses sight of the agony, the emotional strain and, above all, the trauma of the caregivers in their search for answers as they care for the infected. This scenario has prompted the author to look into the theology of caring with an emphasis on pastoral care of the carers with a view of alleviating their emotional burden in caring for the HIV patients.